2018
DOI: 10.1002/polb.24593
|View full text |Cite
|
Sign up to set email alerts
|

Thin poly(ionic liquid) and poly(vinylidene fluoride) blend films with ferro‐ and piezo‐electric polar γ‐crystals

Abstract: Ferro-and piezo-electric poly(vinylidene fluoride) (PVDF) thin film is reported to be obtained by using a poly(ionic liquid) (PIL) [poly(2-(dimethylamino)ethyl methacrylate) methyl chloride quaternary salt] through solution route. The short range interactions between localized cationic ions of PIL and polar >CF 2 of PVDF are responsible for modified polar c-PVDF (T 3 GT 3 G) formation. Modification in chain conformation of PVDF is confirmed by FTIR, XRD, and DSC studies suggesting the miscible PVDF-PIL (PPIL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…An example is illustrated here by the combination of poly(vinylidene fluoride) (PVDF) with a poly(2-(dimethylamino)ethyl methacrylate) methyl chloride; in this case a film is fabricated through noncovalent interactions between the localized cationic ions of the PIL and the polar -CF 2 group of PVDF, which results in a PIL-PVDF composite film featuring excellent ferroelectric properties. 140 PIL-polymer membranes are useful in electrochemical devices. In particular, PIL-based electrolytes are selected for memory devices because of their advantages of mechanical stability, safety, good processability and moderate ionic conductivity.…”
Section: Pil-organic Polymer Compositesmentioning
confidence: 99%
“…An example is illustrated here by the combination of poly(vinylidene fluoride) (PVDF) with a poly(2-(dimethylamino)ethyl methacrylate) methyl chloride; in this case a film is fabricated through noncovalent interactions between the localized cationic ions of the PIL and the polar -CF 2 group of PVDF, which results in a PIL-PVDF composite film featuring excellent ferroelectric properties. 140 PIL-polymer membranes are useful in electrochemical devices. In particular, PIL-based electrolytes are selected for memory devices because of their advantages of mechanical stability, safety, good processability and moderate ionic conductivity.…”
Section: Pil-organic Polymer Compositesmentioning
confidence: 99%
“…Interestingly, Tiwari et al 201 have shown the formation of the γ phase in PVDF upon the incorporation of a poly(ionic liquid), poly(2-(dimethylamino)ethyl methacrylate) methyl chloride quaternary salt. Here, the poly(ionic liquid) is added to the PVDF in solution at loadings up to 50 wt% and thin films are then solvent cast.…”
Section: Composites Additives and Nanoscale Fillersmentioning
confidence: 99%
“…Among these phases, the α-phase is a nonpolar phase and can be used only as ordinary plastic. The polar β- and γ-phases, especially the γ-phase serve as a rather good candidate for fabricating thermally stable devices with long endurance because of its excellent thermodynamic stability and the highest Curie temperature. , They are, however, not easily obtained. , There are two types of γ-PVDF crystallites discriminated from their formation procedures. One of them, designated as γ form, is obtained directly from the melt crystallization at extremely high temperatures.…”
Section: Introductionmentioning
confidence: 99%